Literatur Review : Analisis Pemanfaatan Sistem Informasi Mobile Terhadap Kualitas Pelayanan Kesehatan - Mergiono, Sigit (Universitas Pelita Bangsa, 2024)
The development of mobile technology has changed the healthcare landscape, providing new opportunities to improve service quality. This article aims to analyze the use of mobile applications on healthcare quality. Through System Literature Review (SLR) research, we investigate the extent to which the use of mobile applications by patients, medical personnel, and healthcare providers can improve efficiency, accessibility, and customer satisfaction. This study identifies factors that influence the use of mobile apps in the healthcare environment and analyzes their impact on the interaction between patients and providers. The results show that the utilization of mobile apps significantly contributes to the improvement of service quality, by reducing waiting time, improving communication, and providing better access to health information.